2011
DOI: 10.14430/arctic4078
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Ecology of Birds at Teshekpuk Lake: A Key Habitat Site on the Arctic Coastal Plain of Alaska

Abstract: ABSTRACT. The Teshekpuk Lake Special Area in the National Petroleum Reserve -Alaska (NPR-A) currently has no long-term protection from oil development. In this study, we provide novel information on nest density, productivity, and habitat use at Teshekpuk relative to a developed oilfield site at Prudhoe Bay, Alaska, to assess the importance of Teshekpuk for tundra-nesting birds and to provide recommendations regarding potential oil development. Mean annual nest density of all bird species combined was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…The estimated DSR for Smith's Longspur nests was consistently high compared with that of Lapland Longspurs and Savannah Sparrows (Passerculus sandwichensis) breeding in the north (Weatherhead 1979, Martin et al 2009, Liebezeit et al 2011. We attribute the high and consistent rates of nest success of Smith's Longspurs in part to the species' polygynandrous mating system, in which females typically nest in neighborhoods and may benefit from soliciting copulations from multiple males, subsequently assuring additional care for offspring (Davies 1985).…”
Section: Model Namementioning
confidence: 79%
“…The estimated DSR for Smith's Longspur nests was consistently high compared with that of Lapland Longspurs and Savannah Sparrows (Passerculus sandwichensis) breeding in the north (Weatherhead 1979, Martin et al 2009, Liebezeit et al 2011. We attribute the high and consistent rates of nest success of Smith's Longspurs in part to the species' polygynandrous mating system, in which females typically nest in neighborhoods and may benefit from soliciting copulations from multiple males, subsequently assuring additional care for offspring (Davies 1985).…”
Section: Model Namementioning
confidence: 79%
“…For example, loons that require large lakes for breeding and foraging [70] were most abundant in flat areas with high amounts of freshwater; gulls, which often breed on marshy hummocks, raised beaches, and inland tundra around large ponds [71], [72], were most abundant in the same habitats as loons. Shorebirds were most abundant in flat areas with high vegetative productivity, as predicted based on habitat preference [64]. The amount of freshwater present may not have influenced overall shorebird abundance because some species prefer well drained, sparsely vegetated tundra (e.g., American golden-plovers), while others prefer wet, marshy habitats (e.g., sandpipers and phalaropes) [73].…”
Section: Discussionmentioning
confidence: 99%
“…Liebezeit et al. () report that fox density is higher in Prudhoe Bay than at a site near Teshekpuk Lake, and Liebezeit and Zack () found that fox density is higher at Prudhoe Bay than at a site on the Ikpikpuk River west of Teshekpuk Lake.…”
Section: Discussionmentioning
confidence: 99%
“…Liebezeit et al. () compared nesting success at sites in Prudhoe Bay and near Teshekpuk Lake and found no significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation